Mechanical in building services: Permaisuri Resort & Hotel / Muhammad Kamil Akram Zainal Abidin - Zainal Abidin, Muhammad Kamil Akram (2013)
In this practical report contains information and detail about property company, the owner of the building and others. Experience about how to conduct the mechanical and electrical services in residence building. The position that I had at PRPD is maintenance staff. This report contain about what is mechanical in engineering term and what is mechanical system in building services with same word in different meaning. In time my practical, my case study and report will cover a little more about mechanical facilities and system such as lift, fire alarm, water supply pump, cooling tower, air – condition and other else. Overall, this practical report is very simple. It can explain about what is mechanical in engineering and what its cover. After that, what is mechanical in building services term and what its cover. I’m also show that what I have learn and what have I do and proposed to maintenance department to do more better then that when financial is lack.